Cultural diversity and innovative entrepreneurship - Paula Prenzel; Niels Bosma; Veronique Schutjens; Erik Stam (Small Business Economics, 2024)
A growing empirical literature has established a positive relationship between cultural diversity and entrepreneurship, often attributing this effect to innovation benefits of diversity. However, not all entrepreneurship is inherently innovative, raising the question of whether cultural diversity may increase the likelihood of an entrepreneur pursuing an innovative instead of a more replicative business strategy. This study investigates the relationship between regional cultural diversity and the innovation~orientation of early-stage entrepreneurs and considers moderating factors by decomposing shares of foreign-born population by origin (within and outside of the EU) and by education level. Combining survey data from the Global Entrepreneurship Monitor with population-based indicators of cultural diversity, we carry out a multilevel analysis for 140 European regions. The results suggest that entrepreneurs in culturally more diverse regions are significantly more likely to exhibit innovation~orientation.
Keywords: F22; L26; O30; R1; 330; Cultural diversity; Entrepreneurship; Innovation; European regions; Multilevel analysis